Anti-fouling properties of a protective coating based on alkyd enamel modified with a hydrophobic cationic biocide - Rogalsky, S.P.; Moshynets, O.V.; Dzhuzha, O.V.; Tarasyuk, O.P.; Morozovska, I.O.; Protasov, O.O. (Problems of Environmental Biotechnology, 2023)
New hydrophobic cationic biocide 1-dodecylpyridinium dodecylbenzenesulfonate (PyrC12-DBS) has been synthesized and evaluated as antifouling additive for protective coating based on alkyd enamel. Protective coatings, containing 10 weight percent of cationic biocide, were found to have high resistance to biofouling by aqueous micro- and macroorganisms.